PINK1 Deficiency Ameliorates Cisplatin-Induced Acute Kidney Injury in Rats - Zhou, Li; Zhang, Ling; Zhang, Yu; Yu, Xuan; Sun, Xiuping; Zhu, Tao; Li, Xianglei; Liang, Wei; Han, Yunlin; Qin, Chuan (Frontiers in Physiology, 2019)
Removal of damaged and depolarized mitochondria, known as mitophagy, is critical to cellular homeostasis and viability. Although initially identified in neurodegenerative diseases, mitophagy is being recognized as playing important roles during acute kidney injury. PINK1 and Parkin play central roles in regulating mitophagy. Here, we used PINK1 knockout rats to examine the role of PINK1/Parkin-mediated mitophagy in cisplatin nephrotoxicity. Compared with wild-type rats, PINK1 knockout rats showed lower serum creatinine and less tubular damage following cisplatin treatment. Meanwhile, mitophagy indicated by autophagosome formation and LC3B-II accumulation was also attenuated in PINK1 knockout rats. Renal expression of PINK1 and Parkin were downregulated while BNIP3L was upregulated by cisplatin treatment, indicating a major role of BNIP3/BNIP3L pathway in cisplatin induced mitophagy. Transmission electron microscopy showed that PINK1 deficiency inhibited cisplatin induced mitochondrial fragmentation indicating an involvement of mitochondrial fusion and fission. Renal expression of mitochondrial dynamics related proteins including Fis1, Drp1, Mfn1, Mfn2 and OPA1 were checked by realtime PCR and western blots. The results showed PINK1 deficiency distinctly prevented cisplatin induced upregulation of Drp1. Finally, PINK 1 deficiency alleviated cisplatin-induced tubular apoptosis indicated by TUNEL assay as well as the expression of caspase3 and cleaved caspase3. Together, the results suggested PINK 1 deficiency ameliorated cisplatin-induced acute kidney injury in rats, possibly via inhibiting Drp1 mediated mitochondrial fission and excessive mitophagy.